PERAN MANELEO DALAM PERKAWINAN ADAT USIA DINI DI DESA KULI AISELE KABUPATEN ROTE NDAO - Yeriko Suilima; Juliana Susantje Ndolu; Rini Marselin Kaesmetan (STKIP Subang, 2026)
This study examines the role of Maneleo in early-age customary marriage practices in Kuli Aisele Village, Rote Ndao Regency, and its impact on the social and cultural life of the community. The problem addressed is the persistence of early-age marriage despite national law setting the minimum marriage age at 19 years. The objective of this study is to identify the role of Maneleo as a customary authority and to analyze the resulting impacts. This research uses an empirical method with a descriptive qualitative approach, collecting data through interviews, observations, and literature studies. The respondents include Maneleo, community leaders, and couples involved in early-age marriages within the last five years. The findings show that Maneleo plays a dominant role as the highest customary authority in determining the legitimacy of marriage, acting as a mediator and negotiator in determining bride wealth (belis), leading traditional rituals, and preserving cultural values. This role contributes to the continuation of early-age marriage as part of tradition and social stability. The impacts are both positive and negative, including cultural preservation and strengthened kinship, as well as socio-economic risks, disrupted education, and potential conflicts with state law. Therefore, collaboration between customary institutions and the government is necessary through education and policy integration.